The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/ccm.0000000000001723
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Oximetry During Cardiac Arrest: A Multicenter Study of Neurologic Outcomes and Survival*

Abstract: Cerebral oximetry allows real-time, noninvasive cerebral oxygenation monitoring during cardiopulmonary resuscitation. Higher cerebral oxygenation during cardiopulmonary resuscitation is associated with return of spontaneous circulation and neurologically favorable survival to hospital discharge. Achieving higher regional cerebral oxygenation during resuscitation may optimize the chances of cardiac arrest favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…However Storm et al [ 31 ] when investigating the effect of cerebral oxygenation during CPR found that a low value at the beginning of treatment on arrival of emergency services was not a good predictor of ROSC or neurological outcome. In contrast, Parnia et al [ 32 ] found that in IHCA, cerebral oxygenation values were a significant predictor of a neurologically favourable survival.…”
Section: Discussionmentioning
confidence: 92%
“…However Storm et al [ 31 ] when investigating the effect of cerebral oxygenation during CPR found that a low value at the beginning of treatment on arrival of emergency services was not a good predictor of ROSC or neurological outcome. In contrast, Parnia et al [ 32 ] found that in IHCA, cerebral oxygenation values were a significant predictor of a neurologically favourable survival.…”
Section: Discussionmentioning
confidence: 92%
“…While methods exist for monitoring cerebral oxygen content perioperatively, no standardized method of continuous cerebral oxygen monitoring currently exists for patients undergoing an out-of-hospital (OHCA) or in-hospital CA (IHCA). Parnia and colleagues state that the ability to detect and quantify cerebral ischemia in real-time, during CPR is of vital clinical importance [ 85 ]. Patients, with a post-clinical determination of CA have suboptimal levels of cerebral oxygen content which may lead to secondary ischemic injuries (i.e., sterile inflammatory cascade).…”
Section: Brain Oxygen Monitoringmentioning
confidence: 99%
“…NIRS utilizes infrared light (700–1100 nm) to determine the difference in absorption between oxyhemoglobin and deoxyhemoglobin [ 91 ]. The use of near-infrared spectroscopy during CPR has produced multiple studies resulting in a correlation between higher regional oxygen saturation and a higher chance of return of spontaneous circulation [ 85 , 92 , 93 ]. However, another study indicated that the high regional oxygen saturation and possibility of return of spontaneous circulation was not significant to determine survivability to discharge [ 94 ].…”
Section: Brain Oxygen Monitoringmentioning
confidence: 99%
“…A higher rSO 2 or increases of rSO 2 have been shown to be strongly associated with ROSC and survival with favorable neurological outcome. [1][2][3][4] We have previously reported on the serial changes observed in cerebral rSO 2 values during resuscitation in patients with out-of-hospital cardiac arrest (OHCA). Although chest compression by itself could not increase the cerebral rSO 2 value, ROSC and the initiation of extracorporeal CPR increased the cerebral rSO 2 value.…”
Section: Introductionmentioning
confidence: 99%